ANALISIS PRODUKTIVITAS USAHATANI CABAI MERAH BESAR (Capsicum annum L.) DI DESA ANDONGSARI KECAMATAN AMBULU KABUPATEN JEMBER - Indira Nofita; Syamsul Hadi (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2015)
The purpose of this study was to compare the productivity of land based on land strata and determine the factors that affect the farming production of red chili pepper. This research method using descriptive method with survey techniques. The research location at Andongsari Ambulu Jember. Data collecting techniques using direct interviews. Primary and secondary data were analyzed by quantitative analysis, the average difference test and regression analysis by F test, LSD test, and t test. The result of this study are : (1) The level of productivity of the land by broad strata of business showed no difference between small and medium-scale enterprises, medium and wide-scale efforts are significant,whereas among business scale narrow and broad, showed no difference in significant productivity, and (2) factors that significantly affect production of red chili pepper that are seeds, labor and education, while the number of fertilizers, pesticides, age, and experience are not that significantly affect production of red chili pepper.Keywords: productivity, production, red chili